2002
DOI: 10.1359/jbmr.2002.17.9.1621
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Adult Vertebral Cancellous Bone: Correlation With Collagen Intermolecular Cross‐Links

Abstract: Although the mechanical strength of cancellous bone is well known to depend on its apparent density, little is known about the influence of other structural or biochemical parameters. This study specifically investigates the cross-linking of the collagen in human vertebral bone samples and its potential influence on their mechanical behavior. Multiple cylindrical samples were cored vertically in the vertebral bodies of nine subjects (aged 44 -88 years). Three spinal levels (T9, T12 or L1, and L4) and three sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
138
3
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(162 citation statements)
references
References 33 publications
14
138
3
5
Order By: Relevance
“…25,29,30 Only one ex vivo study performed in human vertebrae reported that the ratio of PYD/DPD in human vertebral trabecular bone was significantly associated with elastic modulus and ultimate strength, but the interpretation of the PYD/ DPD ratio is challenging. 28 We also did not observe any association between PEN content and mechanical properties before or after adjustment for BV/TV. Several prior studies found that higher levels of AGEs are associated with decreased postyield properties of cortical and trabecular bone.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…25,29,30 Only one ex vivo study performed in human vertebrae reported that the ratio of PYD/DPD in human vertebral trabecular bone was significantly associated with elastic modulus and ultimate strength, but the interpretation of the PYD/ DPD ratio is challenging. 28 We also did not observe any association between PEN content and mechanical properties before or after adjustment for BV/TV. Several prior studies found that higher levels of AGEs are associated with decreased postyield properties of cortical and trabecular bone.…”
Section: Discussioncontrasting
confidence: 51%
“…[23][24][25][26][27] Whereas the content of PYD and DPD in bone matrix were related to bone strength in the lathyric model, in ex vivo studies, the role of these enzymatic cross-links remains unclear. 25,26,28,29 In comparison, the accumulation AGEs such as pentosidine (PEN) in the bone matrix is consistently associated with impairment of the postyield properties of trabecular and cortical bone. 24,25,29,30 Few of these studies were performed on human trabecular bone, thus the role of collagen crosslinks on trabecular bone mechanical behavior remains unknown.…”
mentioning
confidence: 99%
“…Banse et al 35 showed that the ratio between the enzymatic crosslinks PYD / DPD, but not their actual concentration, was significantly associated with the compressive biomechanical properties of human vertebrae independent of BMD. There was no association of divalent immature crosslinks or pyrolle with mechanical properties.…”
Section: Collagen Post-translational Modifications and Bone Strengthmentioning
confidence: 99%
“…There are two types of cross-links: enzymatically and non-enzymatically (Seigmund et al, 2008). Considering the macroscopic response of bone, enzymatic cross-linking has been related to improving mechanical properties (Banse et al, 2002) whereas non-enzymatic cross-linking prevents energy absorption by micro damaged formations and may accelerate brittle fracturing Tang et al, 2007;Nyman et al, 2007;Vashishth, 2007). Natural cross-linking gives collagen a high tensile strength and proteolytic resistance (Friess, 1998).…”
Section: Introductionmentioning
confidence: 99%